آلية تحريك الدعوى أمام المحكمة الجنائية الدولية والتحقيق فيها (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعد المحكمة الجنائية الدولية الهيئة القضائية الدولية الجنائية المختصة النظر في الجرائم ضد الإنسانية وجريمة الإبادة الجماعية وجرائم الحرب وجريمة العدوان. ويتم تحريك الدعوى الجنائية أمام هذه المحكمة بإحدى الوسائل التالية: الأولى يطلق عليها إحالة "الحالة" حيث تدخل الدعوى أو الحالة أمام المحكمة بناءً على طلب يتقدم به مجلس الأمن الدولي أو إحدى الدول الأطراف أو غير الأطراف بناءً على شروط وإجراءات محددة بشكل دقيق. أما الوسيلة الثانية فقوامها تحرك المدعي العام للمحكمة الجنائية الدولية وتدخله من تلقاء نفسه لإجراء تحقيق في إحدى الجرائم المذكورة ودونما أحالة. وبناءً على ما تقدم فإن البحث يتناول الطرق الثلاث لوصول الدعوى الجنائية أمام المحكمة الجنائية الدولية وإجراء التحقيق فيها. The International Criminal Court is considered the judicial body specialized in the crimes against humanity, genocide, crimes of war, and the crime of aggression. A case is brought before the court by one of the following means. The first is called referral of the "case" where the case is transferred to the court by the Security Council or one of the parties involved or not involved, based on very specific conditions and procedures. The second is when the prosecutor of the International Criminal Court interferes for investigating one of the aforementioned crimes without waiting for any transference. This paper studies the three methods mentioned for a case to reach the International Criminal Court and to start an investigation.